Analisa Kekasaran Permukaan Pada Proses Edm Sinking Menggunakan Metoda Response Surface Methodology - Eko Yudo; Zaldy Kurniawan (Manutech : Jurnal Teknologi Manufaktur, 2018)
The development of technology in the manufacturing sector is very fast, the market demand is diverse will the needs of products and components with complex shapes and high level of precision and hardness of material that has high strength. High degree of hardness and precision are widely used nonconventional EDM machine sinking. the electrode wear rate (LKE) and surface roughness (KP) are at least the performance of the EDM sinking machine process to be achieved. The study was conducted to determine the contribution of process parameters in order to reduce the variation of response parameters simultaneously and to determine the appropriate process parameter setting value. Parameters varied current, on time, off time and machining voltage. This research uses experimental design from Response Surface Methodology (RSM) method. And obtained the most refined Ra roughness results on Ton 100 µs, and Toff 15 µs with 10 A Ampere, and the roughest Ra roughness is obtained at Ton 300 µs, and Toff 15 µs with Ampere 20 A.